A High‐Performance Self‐Powered Photodetector Based on Monolayer MoS2/Perovskite Heterostructures. Issue 6 (15th January 2018) - Bai, Fan; Qi, Junjie; Li, Feng; Fang, Youyin; Han, Weipeng; Wu, Hualin; Zhang, Yue
Abstract: Here, it is first reported that a self‐powered photodetector based on a MoS2 /CH3 NH3 PbI3 vertical type heterojunction, which has responsivity of 60 mAW −1 and response/recovery time of 2149/899 ms. Under bias, it exhibits a photoswitching ratio exceeding 1522, fast response/recovery time of 205/206 ms, and high photoresponsivity of 68.11 AW −1 . The optoelectronic performances of the photodetector are closely related to the type of the MoS2 /CH3 NH3 PbI3 heterojunction, which acts as a hole (electron) transport field and can effectively decrease the recombination of holes and electrons. Additionally, the MoS2 /CH3 NH3 PbI3 planar type heterojunction is also built to compare with the vertical type in optoelectronics behavior. Due to the existence of internal field, the properties of vertical type photodetector are better than those of the planar type which also presents good performance with on/off ratio up to 1476, photoresponsivity of 28 AW −1, and response rate of 356/204 ms. These results pave a new way to form an ultrahigh performance MoS2 /CH3 NH3 PbI3 heterojunction, hold the promise for construction of a self‐powered photodetector, and develop promising atomically thin MoS2 heterostructure device for photovoltaic and optoelectronic applications. Abstract : A self‐powered photodetector based on a MoS2 /CH3 NH3 PbI3 vertical type heterojunction with high photoresponse is first reported, which is attributed to the buit‐in electric field formed at interface of MoS2 /CH3 NH3 PbI3 heterojunction.